RISK DECREASE PROBLEM WITH MAKING ERRORS IN ACTIVITY OF OPERATORS DEALING WITH AUTOMATIC CONTROL SYSTEMS OF GAS-DISTRIBUTION STATIONS - V. V. Egorov; M. El-Greyd (Наука и техника)
The paper contains an analysis of specific features pertaining to the activity of operators dealing with automatic control systems of gas-distribution stations. The professional operator’s activity is presented in the form of the developed data model. Possible conceptual approaches to the research are analyzed in the paper. The paper describes an author’s approach to studying a risk decrease problem in the activity of operators on the basis of the analytical research results. Technology for obtaining  research results is cited in the paper.